2005
DOI: 10.1590/s0101-20612005000400029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chickpea (Cicer arietinum L.) germination on the major globulin content and in vitro digestibility

Abstract: A quem a correspondência deve ser enviada. SUMMARYChickpea seed germination was carried out over a period of 6 days. Little variation in the nitrogen and total globulin content was observed. The major globulin (11 S type) showed higher variation after the 4 th day of germination. The elution behaviour and distribution of the isolated major globulin fraction on Sepharose CL-6B chromatography showed little modification at the end of germination. On SDS-PAGE the peak eluted from Sepharose CL-6B showed changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…BR‐14 mulatto. Portari et al 30 found in vitro digestibility values of 72.4% and 76.9% for chickpea meal and the total globulin, respectively, while Neves et al 21 found 68.7% and 83.0% for total protein and total globulins from sweet lupin, respectively. Monsoor and Yusuf31 using the pepsin–pancreatin sequence of digestion observed 93.4%, 95.2% and 89.0% digestibility for protein concentrates from pea ( Lathyrus sativus ), lentil ( Lens culinaris ) and chickpea ( Cicer arietinum ), respectively; these values were higher than those reported for legume proteins in general and for their native form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BR‐14 mulatto. Portari et al 30 found in vitro digestibility values of 72.4% and 76.9% for chickpea meal and the total globulin, respectively, while Neves et al 21 found 68.7% and 83.0% for total protein and total globulins from sweet lupin, respectively. Monsoor and Yusuf31 using the pepsin–pancreatin sequence of digestion observed 93.4%, 95.2% and 89.0% digestibility for protein concentrates from pea ( Lathyrus sativus ), lentil ( Lens culinaris ) and chickpea ( Cicer arietinum ), respectively; these values were higher than those reported for legume proteins in general and for their native form.…”
Section: Resultsmentioning
confidence: 99%
“…4) revealed two major protein peaks, corresponding to fractions 41 and 76; however, the first peak was eluted near the column void volume ( V o = 203.4 mL). This first peak was very turbid and, although showing high absorbance at 280 nm, it contained very little protein material when quantified by the method of Lowry et al 14 The occurrence of a turbid peak near the void volume in gel filtration chromatography has been recorded for crude preparations of globulins from various seeds, such as soybean, flaxseed, mustard, wheat, amaranth, peas and chickpeas 30, 33–35…”
Section: Resultsmentioning
confidence: 99%
“…This composition change contributes to https://doi.org/10.1016/j.lwt.2019.108599 Received 14 April 2019; Received in revised form 3 September 2019; Accepted 6 September 2019 the process of technological innovation and expanding the options to consumer preferences. In addition, it is important to note that during germination, minerals are released from phytates and also proteins and carbohydrates can be hydrolysed, releasing amino acids and glucose, which could increase their bioavailability (Lemmens et al, 2018;López-Martínez, Leyva-López, Gutiérrez-Grijalva, & Heredia, 2017;Portari, Tavano, Silva, & Neves, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Globulin fraction was found to decrease significantly ( P ≤ 0.05) after malting as well as roasting. Previous studies have reported similar findings where the globulin content decreased from 45.85% to 37.08% after 6 days of germination (Portari et al ., 2005). Whereas albumin fraction was found to increase during malting from 4.16 ± 0.05% to 7.08 ± 0.10%, it decreased to 3.89 ± 0.18% on roasting.…”
Section: Resultsmentioning
confidence: 99%